First record of the West Atlantic Ariopsis felis (Linnaeus, 1766) (Actinopterygii: Siluriformes: Ariidae) in the Mediterranean Sea - SALAH, JEHAD Y.; ABUTAIR, MOHAMMED A.; AL MABRUK, SARA A.A.; ZAVA, BRUNO; CORSINI-FOKA, MARIA; DEIDUN, ALAN; DI NATALE, ANTONIO; CROBE, VALENTINA; TINTI, FAUSTO (Mediterranean Marine Science, 2024)
A single individual of Ariidae was captured in 2022 in the Palestinian waters off the Gaza Strip, eastern Mediterranean. A comprehensive description of the morphological and meristic characters of the specimen was conducted. Molecular identification was performed through sequence analysis of the Cytochrome Oxidase subunit I (COI). The specimen was identified as Ariopsis felis, both morphologically and genetically. The natural range of this species is the western Atlantic and, to the best of our knowledge, the species has never been reported before from Mediterranean waters. The singular occurrence of this fish in the basin prompts further discussion, raising questions about the possible vectors that may be responsible for this new introduction in the Mediterranean Sea.